2015
DOI: 10.1098/rstb.2015.0031
|View full text |Cite
|
Sign up to set email alerts
|

Activities and regulation of peptidoglycan synthases

Abstract: Peptidoglycan (PG) is an essential component in the cell wall of nearly all bacteria, forming a continuous, mesh-like structure, called the sacculus, around the cytoplasmic membrane to protect the cell from bursting by its turgor. Although PG synthases, the penicillin-binding proteins (PBPs), have been studied for 70 years, useful in vitro assays for measuring their activities were established only recently, and these provided the first insights into the regulation of these enzymes. Here, we review the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
185
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(196 citation statements)
references
References 156 publications
(302 reference statements)
7
185
1
3
Order By: Relevance
“…We also tested PBP1b harboring the E 233 M substitution inactivating the glycosyltransferase domain of the protein using the same approach. As expected, ceftriaxone-resistant mutants were not obtained with derivative of BW25113Δ mrcB producing YcbB and PBP1b E 233 M. The limitation of the latter observation is that no or significantly reduced transpeptidase activity is observed when the glycosyltransferase of E. coli class A PBPs is not functional, although the latter enzymes still bind β-lactam antibiotics indicating a properly folded transpeptidase domain (Terrak et al, 1999; Egan et al, 2015; Born et al, 2006; Bertsche et al, 2005; den Blaauwen et al, 1990). PBP1b E 233 M may therefore be deficient in both transpeptidase and transglycosylase activities.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…We also tested PBP1b harboring the E 233 M substitution inactivating the glycosyltransferase domain of the protein using the same approach. As expected, ceftriaxone-resistant mutants were not obtained with derivative of BW25113Δ mrcB producing YcbB and PBP1b E 233 M. The limitation of the latter observation is that no or significantly reduced transpeptidase activity is observed when the glycosyltransferase of E. coli class A PBPs is not functional, although the latter enzymes still bind β-lactam antibiotics indicating a properly folded transpeptidase domain (Terrak et al, 1999; Egan et al, 2015; Born et al, 2006; Bertsche et al, 2005; den Blaauwen et al, 1990). PBP1b E 233 M may therefore be deficient in both transpeptidase and transglycosylase activities.…”
Section: Resultsmentioning
confidence: 55%
“…To assess the role of the transpeptidase activity of PBP1b, the mrcB gene was introduced into plasmid p Trc 99A, and the transpeptidase module was inactivated by the substitution S 510 A (Terrak et al, 1999). It has been previously shown that PBP1b harboring this substitution is able to catalyze in vitro the polymerization of lipid II into glycan strands in the absence of TPase activity (Terrak et al, 1999; Egan et al, 2015). The derivatives of p Trc 99A encoding wild-type PBP1b and PBP1b S 510 A were introduced into the strain BW25113Δ mrcB harboring pJEH12( ycbB ).…”
Section: Resultsmentioning
confidence: 99%
“…Lipid II- meso -diaminopimelic acid (Lipid II- m -DAP) was synthesized using UDP-Mur N Ac-pentapeptide isolated from Bacillus cereus , essentially as described previously 38,39 with the following modifications. Purification was performed over a DEAE-cellulose column using a linear gradient of chloroform/methanol/water (2:3:1 v/v/v) to chloroform/methanol/1 M ammonium bicarbonate (2:3:1 v/v/v).…”
Section: Methodsmentioning
confidence: 99%
“…The zinc-induced decrease of protein biosynthesis led to a partial disappearance of connexin-43 of protein synthesis in neurons [37], but it is unknown whether PGN biosynthesis is inhibited. Further, it is also unclear whether the both TG/TP should be inhibited by the zinc ions [38,39,40]. The other, zinc ions were accumulated in E. coli periplasmic space, in which the zinc ions are spent to the activation of bacteriolysis of the cell wall.…”
Section: Reactive Oxygen Species (Ros) Omentioning
confidence: 99%